2013
DOI: 10.1002/pssb.201384250
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of sandwich-structured composites with an auxetic phase

Abstract: A sandwich-structured composite is a special class of composite materials that is fabricated by attaching two thin but stiff layers to a lightweight but thick core. Composites analyzed in this paper consist of two different materials: auxetic and structural steel. The optimization criterion is minimum compliance for the load case where the frame's top boundary is downward loaded. Outer layers are made of steel while the middle layer is twophase solid material composite. Only the middle layer is optimized by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Composites with auxetic phase were studied in Refs. . We should add here that similar studies, but with different shapes of inclusions (elliptic and star‐like) were discussed earlier by Wojciechowski .…”
Section: Introductionsupporting
confidence: 72%
“…Composites with auxetic phase were studied in Refs. . We should add here that similar studies, but with different shapes of inclusions (elliptic and star‐like) were discussed earlier by Wojciechowski .…”
Section: Introductionsupporting
confidence: 72%
“…Milton however, has shown that isotropic materials with negative Poisson's ratio can exist within the framework of continuum elasticity. Recently, a two‐phased auxetic composite having no voids and built of two typical “positive” materials have been presented by Strek . Naturally, auxetic materials can also be used as a constituent in composite structures and so influence strongly the behavior of resultant composite.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the multilayered curvilinear shell structures have received special attention in the last years. In [10][11][12][13] several mathematical methods have been used to derive analytical expression for the elastic properties of laminated shell composites. As a particular case, in [14], the expression of the effective coefficients for a curvilinear shell composite with perfect contact at the interface is obtained.…”
Section: Introductionmentioning
confidence: 99%